Suitability of warm mix asphalt (WMA) technologies based on performance and energy consumption - Sukhija M.; Saboo N.; Pani A. (My University, 2025)
Studying the effects of material variability on the performance of warm mix asphalt (WMA) is important to understand the benefits of reduced production temperatures. This study compares the performance of five different WMA mixtures prepared with two varying base binders and two different aggregate sources. The rutting, fatigue, and moisture sensitivity of asphalt mixtures were evaluated using cyclic compression test, indirect tensile cracking test, and modified Lottman test, respectively. Additionally, a theoretical analysis was used to compare the energy consumption during the production process. The results indicated that the performance of WMA is a function of the type of the base binder, aggregate source, and the type of WMA technology. Nonetheless, all the WMA mixtures contributed to higher energy savings in comparison to hot mix asphalt (HMA). Based on the ranking framework used in this study, the use of Rediset is recommended to achieve adequate performance and lower energy consumption. © 2023 Informa UK Limited, trading as Taylor & Francis Group.